Studi Perilaku Konsumen Terhadap Pemakaian Minyak Pelumas dengan Metode Markov Chain - Pulansari, Farida; Permithasari, Nila Febriana (Universitas Trunojoyo Madura, 2009)
Automotive community needs will grow rapidly. One of the tools that support the performance of a vehicle is a lubricating oil or more commonTy known as Oli. Various kinds oflu6ricating ozl brands marketed include Mesran Prima XP, Top 1 Syntetic motor oil, Pennzoil SAE, Active Castrol and Repsol Elite Competition. In this study thefocus is the lubricating oil or grease Mesran Prima XP. The problems faced by these oil products are perceived as declining sales of lubricating oil (grease) Mesran Prima XP, the research conducted by_ the method of Markov Chain, in tJie hope ofknowing the percentage of market share achieved by the oil Mesran Prima XP and determine strategies to increase the market share. Percentage ofknown research on the market share steady state conditions of each oil product in the region to the East Surabaya MESRAN PRIMA XP product for 25.99%; and SYNTETIC MOTOR Oil 7.93%; PENNZOIL SAE of 8.59%; CASTRQL ACTIVE is 53.51% and REPSOL ELITE COMPETITION 3.97%.Keywords: Markov chain, SWOT Analysis